Dose reduction by automatic exposure control in multidetector computed tomography: comparison between measurement and calculation. - Lechel U; Becker C; Langenfeld-Jäger G; Brix G; Lechel, U; Becker, C; Langenfeld-Jäger, G; Brix, G (European Radiology, 2009)
The aim of this study was to investigate the potential of dose reduction in multidetector computed tomography (MDCT) by current-modulated automatic exposure control (AEC) and to test the reliability of the dose estimation by the conventional CT dosimetry program CT-EXPO, when an average tube current is used. Phantom measurements were performed at a CT system with 64 detector rows for four representative examination protocols, each without and with current-modulated AEC. Organ and effective doses were measured by thermoluminescence dosimeters (TLD) at an anthropomorphic Alderson phantom and compared with those given by the calculation with CT-EXPO. The application of AEC yielded dose reductions between 27 and 40% (TLD measurements). While good linearity was observed between measured and computed effective dose values both without and with AEC, the organ doses showed large deviations between measurement and calculation. The dose to patients undergoing a MDCT examination can be reduced considerably by applying a current-modulated AEC. Dosimetric algorithms using a constant current-time product provide reliable estimates of the effective dose.